Apakah Bayi Perlu di Jemur pada Pagi Hari? - Nursanti, Ida (Universitas Jenderal Achmad Yani Yogyakarta, 2012)
Background: The neonatal jaundice (icterus neonatorum) is a frequent problem encountered ininfants during the first week after birth. Sixty percents of healthy infants born full term are at riskof neonatal jaundice and 5-12% of infants are at risk of developing severe jaundice. Bilirubinencephalopathy causes severe jaundice/kernicterus and the baby suffering from cernicterus willexperience impaired growth and development. Severe neonatal jaundice can be prevented byutilization of sunlight. Sunlight helps the process of bilirubin degradation as to preventaccumulation of excessive bilirubin in the blood in the newborn.Objective: To determine the effect of utilization of sunlight on the risk of severe icterusneonatorum. To determine the reasons mothers do the utilization of sunlight and the reason themothers have not done proper utilization of sunlight.Methods: This study was an observational study with a prospective cohort design. The study wasconducted with quantitative and qualitative approaches. Sampling used purposive sampling. Thesample size was 86 pairs of mother-infant who met the inclusion and exclusion criteria. The datawas collected using monitoring sheets, check lists, and questionnaires. The qualitative data wereobtained from interviews to 6 respondents. Hypothesis test used chi-square with p<0.05 and 95%Confidence Interval. Analysis of data used univariable, bivariable, and qualitative analyses.Results: There were differences in the proportion of the incidence risk of neonatal jaundiceamong infants who received the good utilization of sunlight with infants who had less utilization ofsunlight. Babies who lacked the benefits of sunlight had a 2.5 times greater chance to experienceneonatal jaundice compared with infant with good benefits of sunlight. The reason why motherstook advantage of sunlight was because they felt confident that the sun could cope with jaundicein infants. They received knowledge about the benefits of sunlight from the information providedby health workers and family. The mothers had enough knowledge about the techniques ofappropriate utilization of sunlight but with less knowledge about the risks of ultraviolet on skin.Conclusion: Infants who benefited less sunlight had higher risk for having neonatal jaundicecompared with infants who benefited adequate sunlight. Keywords: baby born healthy, sunlight, neonatal jaundice